2018
DOI: 10.1371/journal.pone.0197456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial DNA and RNA extraction methods for high-throughput sequencing of FFPE samples

Abstract: Nucleic acid material of adequate quality is crucial for successful high-throughput sequencing (HTS) analysis. DNA and RNA isolated from archival FFPE material are frequently degraded and not readily amplifiable due to chemical damage introduced during fixation. To identify optimal nucleic acid extraction kits, DNA and RNA quantity, quality and performance in HTS applications were evaluated. DNA and RNA were isolated from five sarcoma archival FFPE blocks, using eight extraction protocols from seven kits from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…Two tissue sections were stained with hematoxylin and eosin, and the presence of representative tumor material (>60% tumor cells) was verified by a sarcoma pathologist. Genomic DNA was isolated using the Allprep DNA/RNA Kit (Qiagen) and the truXTRAC FFPE DNA Kit (Covaris Inc.) from fresh frozen tumor and formalin-fixed paraffin-embedded (FFPE) tissue (20), respectively.…”
Section: Extraction and Quantification Of Dnamentioning
confidence: 99%
“…Two tissue sections were stained with hematoxylin and eosin, and the presence of representative tumor material (>60% tumor cells) was verified by a sarcoma pathologist. Genomic DNA was isolated using the Allprep DNA/RNA Kit (Qiagen) and the truXTRAC FFPE DNA Kit (Covaris Inc.) from fresh frozen tumor and formalin-fixed paraffin-embedded (FFPE) tissue (20), respectively.…”
Section: Extraction and Quantification Of Dnamentioning
confidence: 99%
“…However, no consensus has yet been reached to determine the exact moment in which RNA quality and integrity begin to decrease. Probably this fact is due to the interaction of other pre-analytical factors such as preservation type 12 , preservation method 13 , long term storage 14,15 , RNA extraction methodology 16 , among others.…”
mentioning
confidence: 99%
“…34 We objectively compared existing lysis protocols with AFA, which is widely used in other NGS domains but has not been explored as a microbiome tool. [20][21][22] AFA technology has characteristics that led us to consider it as a logical choice for processing microbial samples, such as precise scalability across a broad range of energy levels, isothermal lysis conditions and the ability to process especially lysis-resistant bacterial species by transducing large amounts of acoustic energy. Using identical aliquots of a mouse stool homogenate as the substrate, we found that a one-step AFA protocol yields more DNA and uncovers greater microbiome diversity relative to bead beating.…”
Section: Discussionmentioning
confidence: 99%
“…19 More specifically, AFA employs focused bursts of high-frequency ultrasonic acoustic energy (wavelength 1-3 mm) focused into a discrete zone within a sample vessel held at nearisothermal conditions (thus enabling cell wall lysis without heat-induced damage of nucleic acids). Although AFA has found widespread use in other NGS protocols, [20][21][22] our study represents the first evaluation for use in microbiome sequencing. In addition to the side-by-side comparison of AFA with traditional chemical/mechanical protocols (where a single lysis step was used for both methods), we also tested the efficacy of a sequential AFA-based microbiome lysis technique, which aims to account for variation in bacterial cell wall thickness and rigidity in a microbiome sample.…”
Section: Introductionmentioning
confidence: 99%